ANALISIS KINERJA KEUANGAN PADA BUMDESA JAYA UTAMA DENGAN RASIO LIKUIDITAS, SOLVABILITAS DAN RENTABILITAS (Studi Pada Badan Usaha Milik Desa/BUMDesa Jaya Utama Rokan Hulu) - Ahmad Bansyar; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to determine and analyze the movement of liquidity, solvency, and profitability BUMDesa Jaya Utama estuary during the period 2016-2020. And to investigate the compliance of financial performance BUMDesa Jaya Utama, based on the liquidity ratio, solvency and profitability ratios during the period 2016-2020. This study uses secondary data obtained by the author through, manual reports. and financial statements of the BUMDesa Jaya Utama necessary researcher for the analysis of liquidity, solvency, and profitability. The analysis showed that the analysis of the financial statements of the BUMDesa Jaya Utama the period 2016-2020 based Ratio Liquidity, Solvency and Profitability are: 1) Analysis of the liquidity ratio, current ratio received the title of "good", and at the cash ratio, received the title of "good"; 2) Analysis of the solvency ratio, asset to debt ratio received the title of "very good", and net worth to debt ratio received the title of "no good"; 3) Analysis of the profitability ratio, return on equity ratio, received the title of "very good", and return on assets received the title of "good". Keywords: Financial performance, liquidity, solvency and profitability.